Yoga Comunitario en la Universidad de Otavalo: un aporte a la salud en la comunidad" - Hernández, Ledys. (2017)
The main activities carried out during the project were: 1. Design and foundation of a strategy for the dissemination of the project among citizens 2. Acquisition of the necessary implements to teach yoga classes. 3. Professional volunteering for a certified yoga instructor. 4. Adequacy of space for yoga classes. 5. Establishment of a weekly schedule for classes. 6. Dissemination of the project in the neighborhoods surrounding the University of Otavalo. 7. Yoga classes. 8. Application of health questionnaires to the participants. 9. Development of an investigation on the influence of the practice of yoga in the health of the users as modality of qualification of a student of the career. 10. Demonstrative class as closure of the project. Situation at the beginning of the project execution The program began with 56 subjects, a group made up of residents of the University of Otavalo, full-time teachers and regular students. The ages of the members of the project vary between 16 and 63 years of age. A questionnaire about their general state of health was applied to each one of them and they were asked sign a waiver of liability.